A clinical comparison of high dose and low dose of Suxamethonium - Yadav, RK; Majhi, PC; Tiwari, D (Journal of College of Medical Sciences-Nepal, 2014)
Background: Suxamethonium having its rapid onset and short duration of action makes this drug unique amongst the neuromuscular blocking drugs described so far. However, use of suxamethonium is associated with a large number of undesirable side effects. Objective: To evaluate clinical effects of high and low dose of suxamethonium and to determine whether lower dose of suxamethonium can be used for any beneficial effects in terms of its various adverse effects e.g. cardiovascular responses, post-operative muscle pains and intraocular pressure. Methods: A total of 100 patients were included in this prospective study. All these patients on preoperative clinical evaluation were assessed to have adequate airway. All the patients were divided in two groups, low dose group (group I) and High dose group (group II) with 50 patients in each at random. A standard anesthetic technique was adhered to all the patients and following parameters were observed on comparative basis: a. Fasciculation and post operative myalgia. b. Cardiovascular effects, c. Intraocular pressure. Observation: The incidence of post Suxamethonium pain was significantly greater in group II. Increase in heart rate from baseline was significant in both groups. There was no significant difference between the two groups in the diastolic pressure but rise in systolic blood pressure was significant at all assessment times in both groups. This rise from control was statistically significant. Conclusion: Suxamethonium can be used in lower doses (0.5 mg/kg) in elective cases without airway compromise. It gives benefits of reduced muscle pains, cardiovascular responses and intraocular hypertension. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-2, 1-8 DOI: http://dx.doi.org/10.3126/jcmsn.v9i2.9677